Evaluation of myocardial deformation in patients with Kawasaki disease using speckle-tracking echocardiography during mid-term follow-up. (5th April 2017) - Dedeoglu, Reyhan; Barut, Kenan; Oztunc, Funda; Atik, Sezen; Adrovic, Amra; Sahin, Sezgin; Cengiz, Dicle; Kasapcopur, Ozgur
Abstract: Speckle-tracking echocardiography is a recently developed technique for the evaluation of myocardial deformation or strain. Our objective was to examine strain through a mid-term follow-up of patients with Kawasaki disease. Methods: We explored left ventricular mechanics using speckle-tracking echocardiography in 35 patients with a history of Kawasaki disease at least 6 months after the acute phase. We also included 30 healthy children as controls. Strain data sets were acquired for the quantification of left ventricular global strain, segmental strain, and left ventricular ejection fraction. Results: The mean age of our patients was 25.6±15.4 months. At a median follow-up of 57.5 months (16.5–98.2), although both values were in the normal range, the mean left ventricular ejection proportion of patients (57.3%) was a little lower than that of controls (p⩽0.05). Patient strain values at the basal inferoseptal (20.0), basal anterolateral (19.5), apical septal (23.3), and apical inferior (24.0) segments were lower compared with controls. In all, seven patients had coronary aneurysms during follow-up. Kawasaki disease patients with pyuria had lower left ventricular strain at the mid anterior, mid anteroseptal, apical anterior, and apical inferior segments and global longitudinal strain compared with patients with no pyuria (p⩽0.05). Conclusion: In children with a history of Kawasaki disease, impairment of left ventricular mechanics occurs especially within the left anterior descending artery territories.